Frequency of Metabolic Syndrome among Hypertensive Patients (Ibrahim Cardiac Medical Journal, 2012)
Background: The metabolic syndrome is quite common worldwide and can be found in approximately one third of patients with essential hypertension in whom it considerably increases the risk of cardiovascular and renal events, even in the absence of overt diabetes. The simple and easy identification of metabolic syndrome will help clinicians managing the patients in their daily clinical practice. National Cholesterol Education Programme Adult Treatment Panel III (NCEP ATP-III) criteria are now considered as the valid indicators for detecting the condition. But it has not yet been widely tested in our country. The present study was, conducted to find the frequency of metabolic syndrome and its risk factors in hypertensive individuals.Methods: This cross sectional study was conducted in Hypertension & Research Center, Rangpur over a period of 2 years from January 2010 to December 2011. A total of 573 adult hypertensive  patients (18 years & above) who fulfilled the criteria of hypertension according to JNC-7 were consecutively included  in  the study as case and a total 206 non-hypertensive subjects were included as control. Metabolic syndrome (MS) was defined according to NCEP ATP-III criteria. Lipid profile and blood sugar level were investigated as laboratory parameters. Treatment history of the patients was also recorded.Results: The study showed a 23% prevalence of metabolic syndrome among hypertensives. About 60% of the patients were in their 3rd and 4th decades of life with mean age being 49.5 ± 12.2 years. A male preponderance was observed with male to female ratio being 3: 2. Over 40% of the patients were overweight or obese. More than 10% of males and 40% of females had central obesity. Overweight & obese subjects were staggeringly higher in hypertensives with metabolic syndrome than that in patients without metabolic syndrome (74.8% vs. 30 .1%, p50  years, females,  overweight/obese  and in patients accustomed to sedentary life-style were 1.4, 2.1, 6.9 and 2.2  times higher respectively  than the patients without having these conditions.Conclusion: The study concluded that metabolic syndrome is a highly prevalent condition among hypertensive individuals. Older patients, females with overweight or obesity leading a sedentary life are at higher risk of developing the condition than males below 50 years with normal BMI and active life-style.Ibrahim Cardiac Med J 2012; 2(2): 24-30